PENGGUNAAN MESSAGE APPEALS PADA AKUN INSTAGRAM @PRABOWO (ANALISIS ISI KUANTITATIF DESKRIPTIF MESSAGE APPEALS DALAM MASA KAMPANYE 10 JANUARI 2024 - 10 FEBRUARI 2024) - Lutvia Anjani, Erlin; Surayya Ulfa, Nurist; Nugroho, Adi (Interaksi Online, 2024)
Along with the development of information technology, politicians have begun to campaign themselves through social media, one of which is Instagram. This study aims to identify the use of message appeals or message appeals on the Instagram account @prabowo during the campaign period of January 10 - February 10, 2024. This study categorizes uploads based on the object of the upload and the type of message appeals used. The analysis is seen from the photos or videos and captions or information contained in the upload. The reliability test in this study uses the Holsti Formula and is then described quantitatively. The data used is documentation of uploads on the Instagram account @prabowo during January 10 - February 10, 2024. In terms of upload objects during the campaign period of January 10 - February 10, 2024, the account is dominated by informational appeals in the information subcategory of 98% and education by 1.4%. In the emotional appeals category, the dominant theme is happiness at 78%, followed by romance at 10.3%, and humor at 6.6%. In the uploaded object, the Instagram account @prabowo does not bring up the theme of sadness and fear. From the writing of the description or caption, informational appeals were found as much as 56% and emotional appeals as much as 44%. The informational appeals category is dominated by information 78% then education 21.9%. Meanwhile, the emotional appeals category is dominated by happiness 77.7%, followed by concern 18.5%, and humor 3.7%.